The building blocks of intuitive intelligence - Subiah, Manj (Henry Stewart Talks, 2019)
Strategic intention, Intuition, Knowledge, Skills, Experience, Emotion, Sense making, Effort, Memory, Information processing, Learning, Ethics, Awareness, Foresight, Risk, Cost/benefit, Consequences, Creativity, Imagination